Trend Pembentukan Piroklor Ln2Te2O7, Ln = La, Nd, Eu dan Gd - Ismunandar Ismunandar; Irawan Haryanto; Santi Dewi (Institut Teknologi Bandung, 2003)
As an extension of Weber, F. A. and Schleid, T. work, attempts to prepare Ln2Te2O7, Ln = La, Nd, Sm, Eu and Gd using the solid state reaction have been conducted. The products were characterized using X-ray powder diffraction methods. La2Te2O7 (a = 11,3821 Ã ) was formed with impurities TeO3, La2O2Te and La2TeO6, while for Nd2Te2O7 (a = 11,1564 Ã ) the impurities were TeO3, Nd2O2Te and Nd2TeO6. Both were decomposed above 850 Â°C. Neither Eu nor Gd formed pyrochlore, instead mixtures with dominant phases of Ln2Te2O7.2. It could be supposed that ionic radii of Eu and Gd too small to stabilize pyrochlore structure. Attempts to prepare Bi2Te2O7 and Pb2Te2O7 have not successful yet.